1999
DOI: 10.1161/01.hyp.34.6.1265
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a Paracrine Tubular Renin-Angiotensin System Along the Entire Nephron

Abstract: Abstract-The renin-angiotensin system is a major regulator of body sodium, predominantly through the actions of intrarenal angiotensin II of unclear origin. We show that polarized epithelium of the proximal tubule synthesizes and secretes angiotensinogen at its apical side and that the protein can be detected in urine as a function of dietary sodium. Furthermore, we demonstrate that renin is expressed and secreted in a restricted nephron segment, the connecting tubule, also in a sodium-dependent fashion. A par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
285
1
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(310 citation statements)
references
References 42 publications
18
285
1
6
Order By: Relevance
“…Renin mRNA and protein are expressed in the proximal and connecting tubules, as well as the collecting ducts. 19,[46][47][48][49][50][51][52][53][54] Interestingly, mechanisms for regulating tubular renin seem to be independent of those in the JG cell. 47,48,50,52 Proximal tubular cells express mRNA [54][55][56] and protein 53,57 for ACE and Aogen.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…Renin mRNA and protein are expressed in the proximal and connecting tubules, as well as the collecting ducts. 19,[46][47][48][49][50][51][52][53][54] Interestingly, mechanisms for regulating tubular renin seem to be independent of those in the JG cell. 47,48,50,52 Proximal tubular cells express mRNA [54][55][56] and protein 53,57 for ACE and Aogen.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…Lalouel and colleagues [72,73] have focused on intratubular RAS. Confluent monolayers of conditionally immortalized cells of murine proximal tubules were grown on semipermeable membranes separating apical and basolateral compartments.…”
Section: Angiotensinogenmentioning
confidence: 99%
“…Luminal ANG II has been shown to stimulate Na/H exchange activity on the brush border so the sustained proximal tubule ANG II concentrations in these hypertensive models may be responsible for maintained proximal tubule sodium reabsorption rates and thus contribute to the continued ANG II dependent actions on proximal tubule reabsorption rate. A recent study by Rohrwasser et al (61) demonstrated localization of angiotensinogen mRNA and protein in proximal tubules of mice and detected angiotensinogen from the apical side of mouse proximal tubule monolayers. These investigators also detected angiotensinogen in the urine and renin in connecting tubule cells of the distal nephron.…”
Section: Intrarenal Ang II Levels In Hypertensive Ratsmentioning
confidence: 99%